The adaptive potential of migrant youth in the megapolis: resource availability and the development opportunities (using the example of Dagestanis living in St. Petersburg) - Ekaterina A. Shekera (Социологическая наука и социальная практика)
In the article, within the framework of the resource approach, based on the results of a questionnaire survey, the assessment by the Dagestan youth living in St. Petersburg of their adaptive potential, expressed in the presence of both material and non-material resources, is revealed. The relevance of this study is due to the fact that the success of social adaptation of internal migrants in a new environment largely depends on the available adaptive potential and its constituent resources, as well as the possibilities of its mobilization and building up. Accordingly, it is possible to correct the process of social adaptation by managing the development of certain resources, transferring them into capital. The author provides a distinction between the concepts of “potential”, “capital”, “resource”. The author’s operationalization of the concept of adaptation potential of migrant youth, developed on the basis of the classification of adaptation resources proposed by Yu. M. Pasovets, is presented. The novelty of this study lies in the first attempt to identify the adaptive potential of the Dagestan youth living in St. Petersburg, and its constituent resources. It was revealed that the success of the adaptation process is most influenced by personal-cultural and social (individual) resources. It is concluded that involvement in social activities can be an additional mechanism for successful adaptation, but this potential is practically unrealized due to the low involvement of young people in this type of activity. Accordingly, the results obtained can be used primarily by leaders and activists of public organizations representing the Republic of Dagestan in St. Petersburg to involve youth in public activities, and the data obtained can also be used to correct the process of social adaptation of Dagestan youth at the municipal level and the level of the subject of the federation.